KINERJA KARYAWAN DI MASA PANDEMI COVID-19 - Imam Arrywibowo SU; Ria Rafiqa Rahim; Misna Ariani (Jurnal GeoEkonomi, 2021)
The Covid-19 pandemic has affected organizations in carrying out company activities to remain productive. Government regulations regulate companies to work from home. Therefore, employee performance is important for the survival of the company. This study aimed to determine whether employee performance is influenced by motivation, job satisfaction, and work environment. The population of this study was 53 permanent employees of PT. Mulia Jaya Mandiri Balikpapan, with a saturated sampling technique, the entire population is sampled. Data analysis includes validity test, reliability test, multiple linear regression test, t-test, and F-test. The results show that performance is influenced by motivation, job satisfaction, and work environment. Job Satisfaction partially has a negative and significant effect. And the dominant motivation affects the performance of employees of PT. Mulia Jaya Mandiri Balikpapan.